Coconut productivity and profitability of two important Philippine PCA hybrids: A critical review - Severino S. Magat; Liberty H. Canja; Susan M. Rivera (International Coconut Community Journal, 2007)
To generate indicative information and knowledge on productivity and production economics in growing coconuts, two known hybrids of coconuts in the country are considered in this review. These are: Catigan dwarf x LAGT (PCA 15-1) hybrid; and Malayan red dwarf x BAYT (PCA 15-3) hybrid, tested earlier at the genetic and performance blocks of Zamboanga Research Center of Philippine Coconut Authority (PCA-ZRC), an intermediate growing zone of coconut, coastal-flat area of Western Mindanao. Relevant data from field establishment, maintenance and yields of palms for first 15 years from field-planting (FP) are used in this ex-ante enterprise budgeting and net present value or NPV analyses, considered as practical tools for decision-making in coconut farming and agribusiness. Depending on the planting material used and farm gate copra price levels (Php 10–24/kg), initial harvest year (4 – 5 years), average annual nut and copra yields at early full-bearing and full-bearing stages, the following profitability indices all differed between the two hybrids: annual gross returns and net returns, net present value (NPV), benefit-cost ratio or BCR, and internal rate of return (IRR %). At mature full-bearing stage, annual yields ranged 2.5 – 4.3 tons copra/ha (135 trees). Using a copra price level of Php 16/kg: the average annual net returns at full bearing stage (10-`15 years) reached PhP23,900 – 44,100 (PCA 15-1) and PhP18,500 – 72,200 (PCA 15-3) and NPV (18% interest) at PhP 20-24/kg copra of PhP 26,340 – 41,641(PCA 15-1) and PhP34,288 - 58,304 (PCA 15-3); and BCR of 1.24 and 1.48 and 1.40 – 1.68, for PCA 15-1 and PCA 15-3, respectively. Overall, varietal productivity, long-term sustainability and profitability or economic indices indicate that the logical selection option identified follows: PCA 15-3 > PCA 15-1. (PhP 48.70 = US$1). Implications on coconut planting/replanting, palm productivity and profitability as influenced by the different planting materials are discussed with respect to policies in coconut industry development.